2013
DOI: 10.1158/0008-5472.can-12-0653
|View full text |Cite
|
Sign up to set email alerts
|

Twist1 Induces CCL2 and Recruits Macrophages to Promote Angiogenesis

Abstract: The transcription factor Twist1 induces Epithelial-Mesenchymal Transition and extracellular matrix degradation to promote tumor metastasis. Although Twist1 also plays a role in embryonic vascular development and tumor angiogenesis, the molecular mechanisms that underlie these processes are not as well understood. Here, we report a novel function for Twist1 in modifying the tumor microenvironment to promote progression. We found that expression of Twist1 in human mammary epithelial cells potently promoted angio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 38 publications
(51 reference statements)
5
126
0
1
Order By: Relevance
“…By binding to E-boxes of the ER promoter and downregulating its activity, Twist1 also endows BC cells with resistance to hormone therapy [40]. Additionally, Twist1 involvement in angiogenesis by enhancing expression of the macrophage chemoattractant chemokine (C-C motif) ligand 2 (CCL2) in metastatic BC cells, with subsequent macrophage recruitment towards tumor microenvironment, was also reported [41]. Lastly, Twist1 has also been shown to be implicated in BC invasiveness and metastatic dissemination by regulating ECM degradation.…”
Section: Derailing Of the Akt2/twist Signaling Axismentioning
confidence: 94%
“…By binding to E-boxes of the ER promoter and downregulating its activity, Twist1 also endows BC cells with resistance to hormone therapy [40]. Additionally, Twist1 involvement in angiogenesis by enhancing expression of the macrophage chemoattractant chemokine (C-C motif) ligand 2 (CCL2) in metastatic BC cells, with subsequent macrophage recruitment towards tumor microenvironment, was also reported [41]. Lastly, Twist1 has also been shown to be implicated in BC invasiveness and metastatic dissemination by regulating ECM degradation.…”
Section: Derailing Of the Akt2/twist Signaling Axismentioning
confidence: 94%
“…Recent papers suggest that oncogenes playing key role in transformation might also play a role in protumoral microenvironment properties [42]. This is true for TWIST1 since its overexpression was reported correlated with increased vascularization in breast carcinoma [43].…”
Section: Twist1 Myc and Immune Systemmentioning
confidence: 98%
“…In fact, Twist1 does not directly induce vEGF production by tumor cells but rather chemokines like CCL2 that are attractive for vEGF-producer macrophages. Their homing in tumor microenvironment site and production of vEGF contribute to metastasis [42]. In aggressive NMA neuroblastoma, it was shown that TAMs are correlated to bad prognosis [10].…”
Section: Twist1 Myc and Immune Systemmentioning
confidence: 99%
“…RNA was subjected to complementary DNA (cDNA) synthesis and RT-qPCR using All-in-One First-Strand cDNA Synthesis Kit and All-in-One™ qPCR Mix (GeneCopoeia) according to the manufacturer's protocol. human CCL2 (hCCL2): CAGCCAGATGCAATCAAT GCC, TGGAATCCTGAACCCACTTCT human GAPDH (hGAPDH): GAGAGACCCTCACTG CTG, GATGGTACATGACAAGGTGC 30 …”
Section: Rna Extraction and Real-time Quantitative Polymerase Chain Rmentioning
confidence: 99%